Women writing art history in the nineteenth century : looking like a woman - Fraser, Hilary, 1953- (Cambridge studies in nineteenth-century literature and culture, 2014)
This book sets out to correct received accounts of the emergence of art history as a masculine field. It investigates the importance of female writers from Anna Jameson, Elizabeth Eastlake and George Eliot to Alice Meynell, Vernon Lee and Michael Field in developing a discourse of art notable for its complexity and cultural power, its increasing professionalism and reach, and its integration with other discourses of modernity. Proposing a more flexible and inclusive model of what constitutes art historical writing, including fiction, poetry and travel literature, this book offers a radically revisionist account of the genealogy of a discipline and a profession. It shows how women experienced forms of professional exclusion that, whilst detrimental to their careers, could be aesthetically formative; how working from the margins of established institutional structures gave women the freedom to be audaciously experimental in their writing about art in ways that resonate with modern readers.